GERAKAN LITERASI SEKOLAH DAN UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PESERTA DIDIK DI MI SAMBINAE KOTA BIMA - Trimansyah, Trimansyah (Prodi PGMI STIT Sunan Giri Bima, 2024)
Madrasah is a very good and strategic place to create a quality generation under the expectations of education and learning goals/, but to support this, the important role of all components and various elements is needed to work together to improve the quality of learning and Education, one of which is implementing the school literacy movement as a force to strive for change and development of competence for each student, both in terms of improving the quality of reading, understanding, knowing, broadening insight, strengthening intellect and intelligence, and enriching various scientific information. All these competencies are contained in cognitive, affective, and psychomotor aspects. This is in accordance with what is being implemented by Madrasah Ibtidaiyah Sambina'e Kota Bima in implementing the school literacy movement with several models including: getting students used to reading 15 minutes before starting lessons, grouping students to collaborate and exchanging stories from the reading results, giving assignments to read, provide motivation, discipline, provide new books, and create a civilizing ecosystem. In addition to what has been implemented by madrasas, interconnectivity of various elements is really needed, starting with the involvement of all school members, parents/guardians of students, and the community.